Prototype Design of Carbon Monoxide Box Separator as a Form of Ar-Rum Verse 41 and To Support Sustainable Development Goal`s Number 13 (Climate Action) - Anggara Trisna Nugraha; Dadang Priyambodo (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2021)
The maritime sector is one of the paths to Golden Indonesia 2045. This is because 70% of Indonesia's territory is a sea with an area of ​​3.25 million km2 and is supported by the large potential that can be utilized for the welfare of Indonesia, one of which is as a contributor to foreign exchange with foreign exchange potential from maritime sector amounting to US 28 million to US 56 million. The problem lingers on how to possible solve the problem regarding air pollution without shutting down industrial operations. Many multinational power plants have launched different campaigns in order to minimize the problem like planting trees and the like. But these small growing industries like grilling restaurants have given way to arising problem of air pollution issues On the other hand, the ocean is a contributor to half of the world's oxygen. But in a period of 50 years, areas with minimal oxygen levels in the oceans have increased. The main cause is global warming, one of which comes from increasing levels of carbon monoxide in the air. One of these gases comes from incomplete combustion in motorized vehicles. This is also exacerbated by the growth of motorized vehicles which has increased by 11.5% per year. If left like this, marine life will be destroyed and Indonesia will not reach its peak of glory in 2045. So to overcome this problem, a prototype design of Carbon Monoxide Box Separator was created. This prototype is a combination of detector sensors consisting of MQ7 to detect carbon monoxide, MQ135 to measure air quality, and DHT11 to measure humidity and air temperature, as well as a high voltage system on the L-Box (Lightning Box) which can produce O2 because of the copper plate. on the L-Box will bind the element carbon to carbon monoxide using a voltage of 400 kV. With this prototype design, it is hoped that Indonesia can achieve its glory and also as a form of QS practice. Ar-Rum verse 41 regarding Allah's command to preserve nature and the environment.